Terrecotte votive e contesti funerari. Gli strumenti del rito nella necropoli di Petto di Nòlio di Medma tra V e IV sec. a.C. - Francesconi, Alessandra (O T I V M, 2024)
From the burials of the Greek Age necropolis of Petto di Nòlio di Medma (Rosarno, Reggio Calabria), numerous whole and fragmented terracotta figures have emerged among the various ritual objects and grave goods discovered. These were produced locally, but they present some iconographic models widespread throughout the whole Magna Graecia area between the 5th and 4th centuries BC. They appear to be few compared to the total number of objects found, but they are important evidence of local cults and funerary rituals, like the other ritual elements uncovered in the same context. The terracotta figures, created for symbolic and funerary purposes, probably represent deities and some mythical subjects connected to them. These subjects are mainly linked to the underworld context and they are represented in a standard iconographic style, similar to that found in nearby holy spaces, although of lesser quality in terms of production and quality.